Ombitasvir, paritaprevir, and ritonavir plus ribavirin for chronic hepatitis C virus genotype 4 infection in Egyptian patients with or without compensated cirrhosis (AGATE-II): a multicentre, phase 3, partly randomised open-label trial. (September 2016) - Waked, Imam; Shiha, Gamal; Qaqish, Roula B; Esmat, Gamal; Yosry, Ayman; Hassany, Mohamed; Soliman, Reham; Mohey, Mohammad A; Allam, Naglaa; Zayed, Naglaa; Asselah, Tarik; Hall, Coleen; et al.
Summary: Background: In Egypt, chronic hepatitis C virus (HCV) infection occurs in around 10% of the population (about 8 million individuals), and is a leading cause of liver cirrhosis, hepatocellular carcinoma, and mortality. Although HCV genotype 4 constitutes about 20% of HCV infections worldwide, the prevalence in Egypt is more than 90%. We assessed the efficacy and safety of the two direct-acting antiviral drugs ombitasvir, an NS5A inhibitor, and paritaprevir, an NS3/4A protease inhibitor dosed with ritonavir, plus ribavirin in treatment of chronic HCV infection in Egypt. Methods: AGATE-II was a phase 3, open-label, partly randomised trial in patients with chronic HCV genotype 4 infection recruited from five academic and hepatology centres in Egypt. Patients were HCV treatment-naive or treatment-experienced with interferon-based regimens. Eligible patients were aged 18 years or older, and had been chronically infected with HCV genotype 4 for at least 6 months with a plasma HCV RNA concentration of more than 1000 IU/mL at screening. Patients without cirrhosis were assigned to receive 12 weeks of 25 mg ombitasvir, 150 mg paritaprevir, and 100 mg ritonavir orally once daily plus weight-based ribavirin. Patients with compensated cirrhosis were randomly assigned (1:1) to receive the same treatment for either 12 weeks or 24 weeks. Randomisation was stratified by previous pegylated interferon and ribavirin treatment experience using a web-based interactive response technology system and computer-generated schedules prepared by personnel from the funder's statistics department. Investigators were masked to randomisation schedules and were informed of each patient's assigned treatment by the interactive response technology system immediately after allocation. The primary endpoint was the proportion of patients with a sustained virological response (HCV RNA <15 IU/mL) 12 weeks after the last dose of study drug (SVR12). All patients who received at least one dose of study drugs were included in the primary and safety analysis. This study is registered withClinicalTrials.gov, numberNCT02247401 . Findings: Between Nov 4, 2014, and March 16, 2015, we screened 182 patients with HCV infection, of whom 160 were eligible for inclusion; 100 patients were assessed as not having cirrhosis and were given 12 weeks of treatment, and 60 patients assessed as having cirrhosis were randomly assigned to the 12-week treatment group (n=31) or the 24-week treatment group (n=29). 94 (94%; 95% CI 88–97) of 100 patients in the without cirrhosis group, 30 (97%; 84–99) of 31 patients in the cirrhosis 12-week treatment group, and 27 (93%; 78–98) of 29 patients in the cirrhosis 24-week treatment group achieved SVR12. The most common adverse events in patients without cirrhosis were headache (41 [41%]) and fatigue (35 [35%]). Fatigue occurred in nine (29%) patients in the cirrhosis 12-week treatment group and 11 (38%) patients in the cirrhosis 24-week treatment group, and headache occurred in nine (29%) patients in the cirrhosis 12-week treatment group and in 10 (35%) patients in the cirrhosis 24-week treatment group. Adverse events were predominantly mild or moderate in severity, and laboratory abnormalities were not clinically meaningful. No patients discontinued treatment because of an adverse event. One serious adverse event in the group without cirrhosis was attributed to study drugs by the investigators; the patient had deep venous thrombosis. Interpretation: Ombitasvir, paritaprevir, and ritonavir plus ribavirin for 12 weeks achieved SVR12 in a high proportion of patients and was well tolerated in Egyptian patients with HCV genotype 4 infection with or without compensated cirrhosis. Extension of treatment to 24 weeks in patients with cirrhosis did not improve the proportion of patients achieving SVR12. A shorter duration regimen could be useful to address the significant burden of HCV genotype 4 infection in patients with compensated cirrhosis. Funding: AbbVie.